Analisis Wacana Kritik Sosial Dalam Lagu "Lagu Kritik Lagi" Karya Feast - Abizar Raihan; Amin Sihabudin; Muslimin Muslimin (Social Science and Contemporary Issues Journal, 2024)
Criticism can sometimes be a very important need in life to express yourself or what is in your heart. In reality, human consciousness can make two decisions, namely ignoring or accepting the situation. To reject and condemn it is to worry about it. Examples include musicians through their music, poets through their poetry, and so on. Such criticism can help clean up the wrong governance order. The aim of the research is to find out what songs are on the album Abdi Lara Insani: Edisi Lengkap by Feast. and to find out the analysis of social criticism discourse in the song "Song of Criticism Again" by Feast. Using a qualitative approach with a descriptive method which aims to explain contemporary issues using information presented in the form of words or images. With data collection techniques through observation, documentation and literature study. As well as using the Miles and Huberman model data analysis techniques which include data reduction, data presentation, and drawing conclusions/verification. The researcher uses Teun A. Van Dijk's critical discourse analysis model, because based on discourse analysis, Dijk does not only rely on textual analysis, because texts are only the result of production practices which must also be scrutinized. but also in analyzing how the text was created, in order to gain knowledge of why the text came to be. There are dimensions of text structure, social cognition and social context which are an integral part of Van Dijk's framework. Based on the presentation of data and critical discourse analysis modeled by Teun A. Van Dijk by discussing the overall meaning of the song on the album "Abdi Lara Insani: Edisi Legkap" and the construction of the meaning of social criticism from the lyrics of the song "Song of Criticism Again" by .Feast. It can be concluded that the album Abdi Lara Insani: Edisi Lengkap tells the story of a fictional character named Ali A(bdi) L(ara) I(nsani), a public official who was originally an idealistic young man who was very critical of the leaders in his country in fight for certain ideas but change when faced with wealth and power. Ali, who was arbitrary with his power, like the previous rulers, whom he had previously criticized heavily, was finally sued by the people of the world. Then the results of the research show that the discourse of social criticism in the song "Song of Criticism again" by .Feast is manifested in three dimensions of text structure, social cognition and social context. So "Song of Criticism Again" by .Feast is an effective means of social criticism. This song can provide awareness to the public about the importance of social criticism of the government.